Search for the Specifity of Pope Francis’ Mariology - Wojtczak, Adam (Teologia w Polsce, 2020)
Francis is a Marian Pope. His six-year-long pontificate so far has resulted in a large number of speeches dedicated to Mary (about 130). The repetitiveness of certain themes and expressions allows us to speak about the specificity of his Mariology and to bring out new and original themes. The article does this in two points. The first concerns the methodology of the Francis’ Mariology. It is a “Mariology in context,” salvific-historical, respecting the principle of nexus mysteriorum. Its loci theologici are the Bible, interpreted in its entirety; conciliar Mariology; theologia mentis and theologia cordis, which is born out of religious experience. It has an eminently pastoral colour. The second point, out of a broad thematic range, distinguishes the statements concerning Mary which are close to Francis: The Mother of God – a synthesis of grace and faith; Mary – the personal concretization of the Church; Hodegetria – the first and perfect disciple of Christ; the Handmaid of man; the Icon and Mother of Mercy; the Star of the New Evangelization; the Queen of tenderness.